Association Between Triglyceride-Glucose Index and Diabetic Retinopathy: A Meta-Analysis - Yu, Lanchu; Li, Bingqing (Hormone and Metabolic Research, 2024)
The objective of this study was to assess the relationship between the triglyceride-glucose (TyG) index, a recently proposed marker of insulin resistance, and the occurrence of diabetic retinopathy (DR), a complication associated with cardiovascular risk. This systematic review and meta-analysis aimed to evaluate the association between the TyG index and DR. To achieve the objective of the meta-analysis, an extensive search was conducted on databases such as PubMed, Embase, and Web of Science to identify observational studies with longitudinal follow-up. Random-effects models were employed to combine the findings, taking into account the potential influence of heterogeneity. Twelve observational studies from 11 reports were included in the meta-analysis, which involved 16 259 patients with type 2 diabetes (T2D). Among them, 4302 (26.5%) were diagnosed as DR. Pooled results showed that a higher TyG index was associated with a higher risk of DR [odds ratio (OR) for the fourth versus the first quartile of TyG index: 1.91, 95% confidence interval (CI): 1.44 to 2.53, p<0.001; I2=72%]. Meta-analysis of TyG index analyzed in continuous variable showed consistent results (OR for per 1 unit increment of TyG index: 1.41, 95% CI: 1.08 to 1.86, p=0.01; I2=82%). Subgroup analysis showed that adjustment of HbA1c or the duration of diabetes did not significantly affect the results (p for subgroup difference all>0.05). In conclusion, a high TyG index was associated with the risk of DR in T2D patients.
Keywords: triglyceride-glucose index; diabetic retinopathy; type 2 diabetes; microvascular; meta-analysis